Analysis of Kurikulum Merdeka tools at SMK Bina Sarana Cendekia Bandung - Aurell Vinaya; Naifa Nur Marischa; Salsabilla Meydiawanti; Shafira Putri Amanda (Hipkin Journal of Educational Research, 2025)
This research aims to analyse the challenges and opportunities in preparing and implementing curriculum tools based on the Kurikulum Merdeka at SMK Bina Sarana Cendekia. This study emphasizes the importance of flexible learning and character development through a project-based approach, which are key aspects of the Kurikulum Merdeka framework. Using qualitative research methods, data were collected through interviews, observations, and documentation to gain insights from teachers and staff about their views on the curriculum. The findings reveal that the development of curriculum tools requires continuous teacher training, cross-sector collaboration, and improvements in supporting facilities. Key challenges include a lack of understanding of new elements such as Learning Outcomes (CP), Learning Objectives (TP), and the Flow of Learning Objectives (ATP), as well as difficulties some educators face with technology application. In conclusion, while implementing the Kurikulum Merdeka holds significant potential to enhance the relevance of vocational education to industry needs, it also faces various challenges related to understanding and applying the new elements. Addressing these challenges through intensive teacher training, innovative project-based teaching modules, and strengthened collaboration with industry is essential for effective implementation at SMK Bina Sarana Cendekia.   Abstrak Penelitian ini bertujuan untuk menganalisis tantangan dan peluang dalam penyusunan dan implementasi alat kurikulum berdasarkan Kurikulum Merdeka di SMK Bina Sarana Cendekia. Studi ini menekankan pentingnya pembelajaran fleksibel dan pengembangan karakter melalui pendekatan berbasis proyek, yang merupakan aspek kunci dari kerangka Kurikulum Merdeka. Menggunakan metode penelitian kualitatif, data dikumpulkan melalui wawancara, pengamatan, dan dokumentasi untuk mendapatkan wawasan dari pendidik dan staf mengenai pandangan mereka tentang kurikulum. Temuan ini mengungkapkan bahwa penyusunan alat kurikulum membutuhkan pelatihan berkelanjutan bagi pendidik, kolaborasi di berbagai sektor, dan perbaikan dalam fasilitas pendukung. Tantangan penting termasuk kurangnya pemahaman tentang elemen-elemen baru seperti Learning Outcomes (CP), Learning Objectives (TP), dan Flow of Learning Objectives (ATP), serta kesulitan dalam aplikasi teknologi yang dihadapi oleh beberapa pendidik. Sebagai kesimpulan, pelaksanaan Kurikulum Merdeka menghadirkan potensi yang signifikan untuk meningkatkan relevansi pendidikan kejuruan dengan kebutuhan industri, namun juga menghadapi berbagai tantangan terkait pemahaman dan penerapan unsur-unsur baru. Mengatasi tantangan ini melalui pelatihan pendidik intensif, modul pengajaran berbasis proyek inovatif, dan kolaborasi yang diperkuat dengan industri sangat penting untuk implementasi yang efektif di SMK Bina Sarana Cendekia. Kata Kunci: analisis kurikulum; Kurikulum Merdeka; pengembangan kurikulum; sekolah menengah kejuruan